Detection of Mycobacterium avium subsp. paratuberculosis in retail cheeses from Greece and the Czech Republic - Ikonomopoulos, John; Pavlik, Ivo; Bartos, Milan; Svastova, Petra; Ayele, Wuhib Yayo; Roubal, Petr; Lukas, John; Cook, Nigel; Gazouli, Maria (Applied and environmental microbiology, 2005)
We investigated the presence of Mycobacterium avium subsp. paratuberculosis in retail cheeses from Greece and the Czech Republic. We found that 31.7% and 3.6% of our samples reacted positive by PCR and culture, respectively. Consumption of these cheeses is likely to result in human exposure to M. avium subsp. paratuberculosis, albeit at a low level for viable cells.
Keywords: Česká republika; DNA primery; Řecko; Czech Republic; sýr; sekvence nukleotidů; Polymerase Chain Reaction; polymerázová řetězová reakce; Base Sequence; DNA, Bacterial; DNA bakterií; Cheese; Greece; DNA Primers; elektroforéza v agarovém gelu; Electrophoresis, Agar Gel; Mycobacterium avium; Mycobacterium avium subsp. paratuberculosis